Randomised trial spacer v nebuliser for acute asthma. Issue 3 (March 1995) - Parkin, P C; Saunders, N R; Diamond, S A; Winders, P M; Macarthur, C
Abstract : Sixty hospitalised children with asthma aged 1-5 years were randomised to spacer or nebuliser. A clinical score was measured at baseline and every 12 hours. There were no differences between groups in the score over time, or secondary outcome measures. The spacer is an effective delivery method for young hospitalised asthmatic children.